Valuasi Ekonomi Air Terjun Sipiso-Piso Dengan Travel Cost Method Dan Willingness To Pay - Simanjorang, Lely Pratiwi; Banuwa, Irwan Sukri; Safe'i, Rahmat; Setiawan, Agus (Fakultas Kehutanan Universitas Jambi, 2018)
Sipiso-Piso Waterfall is part of the Lake Toba area which is included in the Indonesian National Tourism Strategy Area. This study aims to determine the characteristics of visitors and the economic value of Sipiso-piso Waterfall. Economic assessments are carried out based on the travel costs incurred by visitors to the natural attractions they enjoy and willingness to pay. This research was conducted by distributing questionnaires to visitors then analyzed with descriptive. Visitors to Sipiso-piso Waterfall natural attractions are dominated by young people (18-30 years), with an education level equivalent to high school, working in the private sector, income levels of 1-4 million per month and are visitors who have no dependents or single . Some visitors come from Karo Regency, Medan City and Pematang Siantar City, come with groups or families. The total travel costs obtained amounted to Rp. 26.4 billion / year and total willingness to pay Rp. 1.2 billion / year. Economic value was obtained at 27.6 billion / year. This shows that the economic value obtained can be taken into consideration by the manager to increase the entrance ticket rate in line with the increase in facilities, facilities and infrastructure.